2021
DOI: 10.1155/2021/5545312
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Identification and Validation of Potential Biomarkers and Pathways for Idiopathic Pulmonary Fibrosis by Comprehensive Bioinformatics Analysis

Abstract: Objective. Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, irreversible, high-mortality lung disease, but its pathogenesis is still unclear. Our purpose was to explore potential genes and molecular mechanisms underlying IPF. Methods. IPF-related data were obtained from the GSE99621 dataset. Differentially expressed genes (DEGs) were identified between IPF and controls. Their biological functions were analyzed. The relationships between DEGs and microRNAs (miRNAs) were predicted. DEGs and pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A year later it was reported that these deregulated miRNAs were associated with some developmental pathways that involved TGFβ1, Wnt, sonic hedgehog, p53, as well as VEGF and their complex regulatory networks [ 49 ]. Today, many studies are focused on evaluating the expression levels of profibrotic and antifibrotic miRNAs, both in the onset and progression of IPF; however, the results obtained still show contradictory expression levels of these miRNAs [ 50 , 51 , 52 , 53 ]. It is probable that these variations are related to the complexity of this lung disease, since it involves multiple genes and signaling pathways [ 29 , 54 , 55 ].…”
Section: Micrornas and Ipfmentioning
confidence: 99%
“…A year later it was reported that these deregulated miRNAs were associated with some developmental pathways that involved TGFβ1, Wnt, sonic hedgehog, p53, as well as VEGF and their complex regulatory networks [ 49 ]. Today, many studies are focused on evaluating the expression levels of profibrotic and antifibrotic miRNAs, both in the onset and progression of IPF; however, the results obtained still show contradictory expression levels of these miRNAs [ 50 , 51 , 52 , 53 ]. It is probable that these variations are related to the complexity of this lung disease, since it involves multiple genes and signaling pathways [ 29 , 54 , 55 ].…”
Section: Micrornas and Ipfmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is a pervasive chronic pulmonary ailment marked by irreversible lung function loss and structural disfigurement attributable to an overproduction of extracellular matrix deposition ( Mei et al, 2021 ), compounded by progressive scarring of lung tissue and interstitial lung disease ( Qian et al, 2021 ). The disease is predominantly observed in middle-aged to elderly men, and its global prevalence is estimated to exceed 3 million people, with an annual incidence rate between 2 and 9 per 100,000 individuals and an escalating trend ( He et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%